A Case of Myocarditis and Near-Lethal Arrhythmia Associated With Interleukin-2 Therapy - Stephanie Wu MD; Anna Sarcon MS, MD; Khuyen Do MD; Jerold Shinbane MD; Rahul Doshi MD; Helga Van Herle MD (SAGE Publishing, 2018)
We present a case of a 48-year-old female who developed myocarditis and near fatal arrhythmias during high dose Il-2 therapy for metastatic renal cancer. On day 5 of therapy, the patient developed sudden onset chest pain, elevated cardiac enzymes and ST segment changes on EKG. Coronary angiogram was normal, however echocardiogram showed reduced ejection fraction and hemodynamic measurements showed elevated bilateral elevated filling pressures. The patient then developed episodes of recurrent ventricular arrhythmia, precipitated by bradycardia and PVC, requiring defibrillation and temporary pacemaker placement. Endomycardial biopsy was nonspecific showing fibrosis with subsequent cardiac MRI showed evidence of myocardial edema, consistent with Il-2 induced myocarditis in the setting of no prior cardiac history. After the discontinuation of Il-2 therapy, the patient displayed clinical improvement as well as improved ejection fraction. This case brings attention to the cardiac toxicities associated with high dose Il-2 therapy including potentially lethal arrhythmias and highlights the importance of careful cardiac screening prior to initiation of treatment.